Isoenzymatic characterization of rice genotypes - Bonow, Sandro; Augustin, Eliane; Franco, Daniel Fernandes; Peters, José Antonio; Terres, Arlei Laerte da Silva (Pesquisa Agropecuaria Brasileira, 2001)
The objective of this work was to characterize isoenzymaticly rice (Oryza sativa L.) genotypes. Rice yields obtained in Rio Grande do Sul, Brazil, are high, due to the high technology and the irrigation system used, associated to the genetic potential of the bred cultivars. Six ancestors contribute with 86% of the genetic make up of used cultivars. As a consequence of this narrow genetic basis, they are closely related and show very similar morphological and agronomical characteristics, which turns the varietal identification difficult. The competition with wild genotypes (red and black hulled rice) is considered to be the greatest problem, because they belong to the same species as cultivated rice. Isoenzymes analysis can be used to study variability and to estimate genetic relations among genotypes. Therefore, polyacrylamide gel electrophoresis was used to characterize, through seeds and seedling leaf tissue, esterase, 6-phosphogluconate dehydrogenase, phosphoglucoisomerase and isocitrate dehydrogenase, and seedling leaf tissue acid phosphatase and aspartate transaminase isoenzymes of cultivars BR-IRGA 409, BR-IRGA 410, BRS 6 (’Chuí’), BRS Taim 7 (’Taim’), BRS Agrisul, INIA Taquari, El Paso L 144 e IRGA 417, and ecotypes of red and of black hulled rice. Cluster analysis, using Jaccard coefficient and unweighted pair-group method arithmetic average (UPGM), allowed to differentiate all genotypes, excluding BRS 6 (’Chuí’) and BRS 7 (’Taim’). Three groups were identified, including, in one of them, red and black hulled rice ecotypes, with 95% degree similarity.